A188 LOW INCIDENCE OF SPONTANEOUS BACTERIAL PERITONITIS IN ASYMPTOMATIC OUTPATIENTS WITH CIRRHOSIS UNDERGOING PARACENTESIS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2018) - Ahmed, O; Rodrigues, D M; Brahmania, M; Patel, K
Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a common sequelae of ascites in patients with decompensated cirrhosis and is associated with significant morbidity and mortality. Current literature suggests SBP rates of 30% in hospitalized patients with decompensated cirrhosis. However, the incidence of SBP in asymptomatic outpatients undergoing large volume paracentesis is thought to be low, though there is a paucity of literature. Nevertheless, current AASLD guidelines recommend that all patients undergoing routine paracentesis have ascitic fluid analysis. Aims: The primary aim of our study was to perform a systematic review and meta-analysis to determine the incidence of SBP in asymptomatic patients undergoing routine large volume outpatient paracentesis. Methods: A systematic search of Medline and EMBASE was performed (to September 2017) along with a manual search of reference lists of retrieved articles. Two authors (OA, DR) independently reviewed articles retrieved. All studies looking at asymptomatic outpatients with decompensated cirrhosis were included. Data was extracted to determine the incidence of SBP (SBP; positive culture and polymorphonuclear cells (PMNs) greater than 250 PMNs/mm 3 ), the incidence of culture-negative neutrocytic ascites (CNNA; PMN count greater than 250 PMNs/mm 3 ), and the incidence of mononuclear bacterascites (MNB; positive ascitic culture but no elevation in PMNs). Pooled analysis was performed on studies when possible. Results: A total of 309 articles were retrieved with 12 studies being included in the review. 7 were peer-reviewed publications while 5 were in abstract form. A total of 1307 patients were included and a total of 3684 paracentesis were performed. 9 studies provided information on SBP, CNNA or MNB while 3 studies did not specifically differentiate in their diagnostic parameters for SBP. The total incidence of any suspected infection (SBP, CNNA or MNB) was 3% (116/3684) of paracentesis. However, the incidence of definite SBP only was 0.5% (9/1728), while the incidence of SBP or CNNA was evident in 1% (24/1728) of paracentesis. The post-diagnosis management was variable between studies (either no treatment, outpatient antibiotics, or hospitalization). Conclusions: There is a low incidence of SBP and CNNA in asymptomatic outpatients with cirrhosis that require LVP. The utility of analyzing routine analysis of all samples in this population is debatable and likely not beneficial. Further studies are required to determine the cost-effectiveness of routine analysis and to determine whether certain subgroups are at higher risk of SBP. Funding Agencies: None